Nutrient requirements and feeding of finfish for aquaculture (CABI, 2002)
This book contains articles on the nutrient requirements and feeding of finfish for aquaculture. Topics include the following: introduction to fish nutrition; marine fishes (European sea bass, Asian sea bass, red sea bream, gilt-head sea bream, Atlantic salmon, Atlantic halibut, Japanese flounder, North American flounder, yellowtail, red drum, southern bluefin tuna, and milkfish); and freshwater fishes (rainbow trout, Arctic char, percids, coregonids, common carp, Indian major carps, tilapia, channel catfish, eel, hybrid striped bass, sturgeon, silver perch, largemouth bass, hybrid bluegill, Brazilian species, snakehead and Pangasius catfish, and baitfish).